'A World Apart': Change in Student Attitudes during the Interwar Period, 1918–1933. (16th September 2022) - Harrington, Neil
Abstract: This article investigates student culture in interwar universities using the relatively neglected material of student magazines. Recent scholarship suggests that students became increasingly politically aware during the interwar period, accompanied by a significant shift in attitudes in the early 1930s. The present research argues that this change in attitudes was largely superficial, and that underlying 'corporate' values remained intact. This is evidenced by the involvement of ex-service students in strengthening corporate culture, and the close identification between these students and immediate 'post-war' students. Certainly, aspects of corporate culture were challenged later in the decade, when alongside the influence of pacifism there was a move from a 'parochial' style of magazine towards more 'serious' and 'political' articles. However, it is argued that this represented a temporary shift in focus, rather than a fundamental change in underlying values. Student attitudes continued to be embedded within an existing framework based on public school values, and reflecting a commitment to patriotism, duty, and social obligation.